2008
DOI: 10.1016/j.jpsychires.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders and subsequent educational attainment in a US national sample

Abstract: As part of a larger investigation of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
337
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 430 publications
(386 citation statements)
references
References 27 publications
28
337
2
5
Order By: Relevance
“…All our ordered measures (psychological distress, life dissatisfaction and poor general health) are estimated using ordered logistic regressions while our dichotomous dependent variable (psychological anxiety) is estimated using a binary logistic model. In line with existing literature (Araya et al, 2001;Breslau et al, 2008;Lindstrom and Rosvall, 2012), all health equations include as controls a range of socio-demographic and job-related characteristics. We augment the model with our set of mutually exclusive binary indicators of employment transitions in order to permit the identification of any underlying differences in health status relative to Nevers.…”
Section: Regression Resultsmentioning
confidence: 65%
“…All our ordered measures (psychological distress, life dissatisfaction and poor general health) are estimated using ordered logistic regressions while our dichotomous dependent variable (psychological anxiety) is estimated using a binary logistic model. In line with existing literature (Araya et al, 2001;Breslau et al, 2008;Lindstrom and Rosvall, 2012), all health equations include as controls a range of socio-demographic and job-related characteristics. We augment the model with our set of mutually exclusive binary indicators of employment transitions in order to permit the identification of any underlying differences in health status relative to Nevers.…”
Section: Regression Resultsmentioning
confidence: 65%
“…17,29 Also supporting the hypothesis are results from studies in general samples that consistently show psychological adjustment to be an important predicting factor for academic competencies and performance, as well as for academic attainment. 30,31 Education and academic attainment is highly correlated with income and occupation and it is one of the most important predictors of health. 32 Thus, considering the importance of psychological adjustment and academic competencies for children's well-being and success in life, it remains critical to study and identify the risk and protective factors contributing to the associations observed between childhood obesity, psychological adjustment and academic competencies.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other social scientific methods, controlled experimentation has a better chance of uncovering specific mechanisms that lead to disparities in mental health detection and service use, and thus, it can speed up scientific discovery. This is especially critical in relation to problems of ethnic minority youth and their families because children's development is rapid; mental health problems must be presented quickly to avoid permanent consequences (Pottick and Warner 2002;New Freedom Commission on Mental Health 2003;Breslau et al 2008). …”
Section: Resultsmentioning
confidence: 99%